Chemoselective reduction of carboxamides. (24th October 2016) - Volkov, Alexey; Tinnis, Fredrik; Slagbrand, Tove; Trillo, Paz; Adolfsson, Hans
Abstract : This tutorial review presents the most prominent protocols developed for chemoselective amide reduction. Abstract : The reduction of amides gives access to a wide variety of important compounds such as amines, imines, enamines, nitriles, aldehydes and alcohols. The chemoselective transformation into these functional groups is challenging due to the intrinsic stability of the amide bond; nevertheless, the ability to reduce highly stable carboxamides selectively in the presence of sensitive functional groups is of high synthetic value for academic and industrial chemists. Hydride-based reagents such as LiAlH4 or diboranes are today the most commonly used compounds for amide reductions, and apart from the substantial amount of waste generated using these methods, they lack tolerance to most other functional groups. This tutorial review provides an overview of the recent progress made in the development of chemoselective protocols for amide reduction and gives an insight to their advantages and drawbacks.